CuS Microspheres as High-Performance Anode Material for Na-ion Batteries. (1st September 2017) - Li, He; Wang, Yunhui; Jiang, Jiali; Zhang, Yiyong; Peng, Yueying; Zhao, Jinbao
Abstract: In this work, CuS microspheres are synthesized by a facile microwave synthesis without any template or additive. As-prepared CuS microspheres display steady reversibility by adopting triethylene glycol dimethyl ether (TEGDME) as the electrolyte solvent and adjusting cut-off voltage to 0.6 − 3.0 V. The discharge capacity stands at 162 mAh g −1 after 200 cycles with the capacity retention of 95.8%. Electrochemical kinetics of CuS electrodes is investigated by electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and galvanostatic intermittent titration technique (GITT) tests. Beyond that, electrochemical reactions of CuS electrodes are explored using ex-situ X-ray diffraction (XRD). As far as we know, it is not only the best performance of CuS electrodes in Na-ion batteries (NIBs) but also the first time that the kinetics and reaction mechanism of CuS in NIBs are investigated.